Pelaksanaan Fungsi Legislasi Dewan Perwakilan Rakyat Daerah Kabupaten Tapin Periode 2024-2029 dalam Pembentukan Peraturan Daerah - Muhammad Rizky Saputra; Muhammad Hadin Muhjad (Lembaga Yasin AlSys, 2026)
The suboptimal implementation of the legislative function of the Regional People’s Representative Council (DPRD) of Tapin Regency is indicated by the low number of Draft Regional Regulations (Raperda) initiated by the DPRD compared with those initiated by the executive. This study aims to analyze the implementation of the legislative function of the DPRD of Tapin Regency for the 2024–2029 period in the formation of Regional Regulations and to identify the factors influencing it. This study used an empirical juridical method with an approach that examines law as both norm and practice in the field. Data were collected through literature review, document study, and interviews. The results showed that procedurally, the formation of Regional Regulations was in accordance with the provisions of laws and regulations, but its implementation was not yet optimal. This condition was reflected in the low level of DPRD legislative initiative, limited capacity of members in legal drafting, diverse educational backgrounds, lack of organizational experience, low public participation, and political dynamics between the legislature and the executive that influenced the discussion process of Draft Regional Regulations. Thus, the implementation of the legislative function of the DPRD of Tapin Regency still faces various internal and external obstacles that affect the quantity and quality of regional legislative products. The implications of this study emphasize the importance of improving the capacity of DPRD members through technical training, institutional strengthening, and optimization of public participation to enhance the effectiveness and quality of Regional Regulation formation in the future.